TEKNOLOGI DALAM PEMASANGAN IMPLAN GIGI DENGAN HYDROXYAPATITE DAN MATERIAL - Halim, Susanna; Susanto, Susanto; Lumbansiantar, Ruben Tutamana; Panjaitan, Angeline Fransisca; Zaharani, Cut Asy Syifa (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This research is motivated by the crucial role of dental implants as a rehabilitation solution for tooth loss, yet they still face challenges related to bone integration, material durability, and procedure optimization. The use of materials such as hydroxyapatite (HA) and modern technologies continues to be developed to address these issues. Therefore, this study focuses on conducting a literature review of recent developments in dental implant materials and procedures. The method used was a descriptive analytical literature review of three relevant primary articles discussing HA/MWCNT synthesis, implant interaction with saliva, and immediate implant placement procedures. Findings from the first article demonstrated that the combination of HA with multiwalled carbon nanotubes (MWCNT) through electrophoretic deposition improved coating uniformity and corrosion resistance. The second article confirmed the safety of the implant material through artificial saliva analysis, which detected no harmful elements after corrosion. The third article demonstrated that immediate implant placement after extraction, with the support of bone graft and antibiotics, effectively maintained tissue structure and improved aesthetics. It was concluded that the selection of innovative materials such as HA/MWCNT and procedural approaches, such as immediate implant placement, significantly contribute to improving the clinical success, aesthetics, and safety of dental implants. ABSTRAKPenelitian ini dilatarbelakangi oleh peran krusial implan gigi sebagai solusi rehabilitasi kehilangan gigi, namun masih menghadapi tantangan terkait integrasi tulang, ketahanan material, dan optimalisasi prosedur. Penggunaan material seperti hidroksiapatit (HA) dan teknologi modern terus dikembangkan untuk mengatasi masalah ini. Oleh karena itu, penelitian ini berfokus untuk melakukan tinjauan literatur terhadap perkembangan terkini dalam material dan prosedur pemasangan implan gigi. Metode yang digunakan adalah literature review deskriptif analitis terhadap tiga artikel utama yang relevan, membahas sintesis HA/MWCNT, interaksi implan dengan saliva, dan prosedur pemasangan implan segera. Temuan dari artikel pertama menunjukkan bahwa kombinasi HA dengan multiwalled carbon nanotubes (MWCNT) melalui deposisi elektroforetik meningkatkan keseragaman lapisan dan ketahanan korosi. Artikel kedua mengonfirmasi keamanan material implan melalui analisis saliva buatan yang tidak mendeteksi unsur berbahaya pasca korosi. Artikel ketiga membuktikan bahwa pemasangan implan segera setelah pencabutan, dengan dukungan graft tulang dan antibiotik, efektif mempertahankan struktur jaringan dan meningkatkan estetika. Disimpulkan bahwa pemilihan material inovatif seperti HA/MWCNT dan pendekatan prosedural seperti pemasangan implan segera secara signifikan berkontribusi pada peningkatan keberhasilan klinis, estetika, dan keamanan implan gigi.